Struktur Naskah Heart of Almond Jelly Karya Wishing Chong Terjemahan Teguh Hari Prasetyo dengan Gaya Realisme dan Genre Tragikomedi - Harahap, Elliza; Efendi, Leni; Birowo, Pandu; Suisno, Edy (Jurnal Cerano Seni : Pengkajian dan Penciptaan Seni Pertunjukan, 2025)
This study aims to analyze the structure of the script Heart of Almond Jelly by Wishing Chong translated by Teguh Hari Prasetyo, et al to find out the dramatic material of the script. The analysis method used to explore the script in structure and texture is the textual analysis method. Heart of Almond Jelly brings the reader or audience as if witnessing what happens in the reality of everyday life, and discusses a lot about the household problems of a married couple. The conclusion obtained from this research is that the script Heart of Almond Jelly by Wishing Chong translated by Teguh Hari Prasetyo has two characters. The main character is Sayoko and the antagonist is Tatsuro. Heart of Almond Jelly is a reinterpretation of the realism script to realize emotional values and character deepening in realizing drama and has a tragicomedy play form and realism style.